Tunable current-mode log-domain universal filter - Prommee, Pipat; Somdunyakanok, Montri; Angkeaw, Krit; Dejhan, Kobchai (My University, 2010)
This paper describes the design of a current-mode universal filter based on log-domain filtering concept. The circuit is a direct realization of a first-order differential equation for obtaining the two integrators loop structure. Lossless integrators are realized by log-domain lossy integrators. The proposed filter comprises only two grounded capacitors and sixteen transistors. Frequency response of the proposed filter can be instantaneously controlled over a very wide frequency range by controlling current. Quality factor is independently controlled by another current. It can be seen that the proposed circuit suites for high-frequency applications. A validated BJT model that used in simulation is operated by a single power supply as low as 2.5V. The wide-range frequency response is controlled over five decades of current controlled. ©2010 IEEE.
Keywords: Electronically-controlled; High-frequency; Log-domain filtering; Low-voltage; Universal filter